Optics f2f : from Fourier to Fresnel - Adams, Charles S. (Physicist); Hughes, Ifan, 1968- (Oxford University Press, 2019)
This textbook on optics introduces key concepts of wave optics and light propagation. The book highlights topics in contemporary optics such as propagation, dispersion and apodisation. The principles are applied through worked examples, and the text is copiously illustrated with more than 240 figures and 200 end-of-chapter exercises.